A New Approach to Operational Creativity - Wilson, William H. (Academy of Management Journal, 1960)
Offers an overview of the operational creativity efforts of Kimberly-Clark Corp. History of its business operation; Problems faced in creative efforts within a large corporation; Reactions of the members of the creative group.